Identification of carotenoids and phenolic compounds in bacteriabased protein isolates using LC and MS techniques - Santikko, Meeri (My University, 2024)
Global food demand is predicted to increase significantly in the future. Therefore, discovering new protein sources of sustainable origin is important. One of these is bacteria-based protein, which has minimal environmental impact compared to traditional animal agriculture. These novel proteins can hold a variety of color pigments and phenolic compounds that may impact their appearance and flavor. By identifying these compounds and their possible contributions to sensory quality, more development can be done to make them more attractive to consumers. In this study we aim to identify the carotenoid and phenolic compound profile of five bacteria protein isolate samples from different cultivations to identify key color pigments and possible off-flavor compounds as well as observe the differences between different samples. The samples were received from Aistila Oy, where the same samples had undergone sensory analyses. The qualitative analysis of carotenoids and phenolics was done using HPLC-DAD and UHPLC-ESI-MS/MS. Carotenoids and phenolic compounds were extracted using solid-liquid extraction, using acetone for carotenoid extraction, and ethyl acetate, methanol, and water for phenolic compound extraction. Identification and characterization of compounds was carried out by combination of available reference standards, mass spectrometry data, including both positive and negative ion modes as well as MS and MS/MS data, retention time, UV/Vis spectral information and literature data of similar HPLC-MS experiments. A total of eight carotenoids and 16 phenolic compounds were observed; seven out of eight and eight out of 16 of which were tentatively identified. Zeaxanthin (m/z 568 [M+H]+.) and its glucosides zeaxanthin dirhamnoside (m/z 860 [M+H]+) and zeaxanthin monorhamnoside (m/z 715 [M+H]+) were observed as major carotenoids in all five samples; approximately 90-100% of observed carotenoid concentrations were identified as zeaxanthin derivatives. Furthermore, beta-carotene was observed in four out of five samples, accounting for roughly 1-5% of observed concentrations. Phenolic acid derivatives were observed to be the most common compound type in all samples. Hydroxybenxoic acid, benzoic acid, coumaric acid derivatives, phenylalanine, and dihydroxyphenyllactic acid derivatives were tentatively identified from all samples. Hydroxybenzoic acid or its derivatives were found to account for 20-50% of observed phenolic concentrations. Future studies are needed for a thorough quantification and identification of all carotenoids and phenolic compounds in the protein isolate, as well as to discover their influence on the product’s appearance, flavor, and odor.
Keywords: bacteria-based protein, carotenoid, HPLC-DAD, HPLC-MS/MS, phenolic acid, phenolic compound, zeaxanthin